Multimodality therapy for management of acute on chronic central vein occlusion to maintain patency of upper arm arteriovenous fistula - Daniel Nguyen, MD; Scott S. Berman, MD, MHA, RVT, FACS, DFSVS (Journal of Vascular Surgery Cases and Innovative Techniques)
Central venous occlusive disease (CVOD) is a challenging problem that frequently leads to the abandonment of an otherwise functional hemodialysis access. Prior central venous access, including tunneled dialysis catheters, are a common predisposing factor. CVOD is typically preceded by an interval period of stenosis and often amenable to simple balloon angioplasty. Occasionally, the use of aggressive techniques, including sharp recanalization and percutaneous thrombectomy, is necessary to restore patency. We describe a case of acute CVOD involving the left axillary, subclavian, and brachiocephalic vein outflow of an upper extremity arteriovenous fistula that required a multimodality approach, including sharp recanalization of a chronic occlusion, large-bore percutaneous thrombectomy system, balloon angioplasty, and stenting to restore patency and salvage the access site.